Characterizing ipsilateral thalamic diaschisis in symptomatic cerebrovascular steno-occlusive patients - Hendrik Bas van Niftrik, Christiaan; Sebök, Martina; Muscas, Giovanni; Piccirelli, Marco; Serra, Carlo; Krayenbühl, Niklaus; Pangalu, Athina; Bozinov, Oliver; Luft, Andreas; Stippich, Christoph; Regli, Luca; Fierstra, Jorn (Journal of cerebral blood flow and metabolism, 2020)
The clinical significance of ipsilateral thalamic diaschisis (ITD) occurring after stroke is unknown. To characterize ITD, we investigate its hemodynamic, structural, and clinical implications. A single-institution prospective cross-sectional study was conducted using 28 symptomatic cerebrovascular steno-occlusive patients undergoing both BOLD-CVR and Diamox-challenged 15(O)-H2O-PET. Follow-up was at least three months. In addition, 15 age-matched healthy subjects were included. ITD was diagnosed based on a BOLD-CVR thalamic asymmetry index (TAI) > +2 standard deviations from healthy subjects. Cerebral blood flow differences were assessed using a PET-based TAI before and after Diamox challenge. Thalamic volume masks were determined using Freesurfer. Neurological status at symptom onset and after three months was determined with NIHSS and mRS scores. ITD was diagnosed in 15 of 28 (57%) patients. PET-TAI before and after Diamox challenge were increased in patients with ITD, indicating an ipsilateral thalamic blood flow decrease. Patients with ITD exhibited a marked ipsilateral thalamic volume decrease as compared to patients without ITD and healthy subjects. Furthermore, patients with ITD had worse NIHSS and mRS at symptom onset and after three months follow-up, even after adjustment for stroke volume. The presence of ITD is characterized by thalamic volume reduction, reduced thalamic blood flow, and worse neurological performance unrelated to stroke volume.